The benefits of using industrialised building system (ibs) in our construction industry - Wan Abdullah, Wan Zukri (2009)
The Industrialized Building System (IBS) has been introduced in Malaysia since 1966 for the projects which involve precast houses. Since then numerous construction projects use the IBS system when necessary whereby the system is implemented when the construction requires speed accuracy and work that involves a lot of repetition. Industrialized in construction industry is part of a process in change and improvement management. The objectives of doing his research are to determine the factors that contractors consider in selecting a mode of construction and also to study the benefit of using IBS compared to the traditional subcontracting system of project management. The main method adopted is by using the questionnaire and interview sessions. The set of questions for interview sessions with the person in charge has to be prepared. Questionnaires together with the cover letter were distributed to the respondents. The respondents were requested to answer the entire questions during the interview session.